STUDI PENGARUH VARIASI PH DAN KOLEKTOR PADA EFISIENSI FLOTASI MINERAL TEMBAGA SULFIDA - Kostiawan Sukamto; Astin Lukum; Akram La Kilo (Jurnal Crystal : Publikasi Penelitian Kimia dan Terapannya, 2025)
This study aims to investigate the effect of pH variations and collector types on the recovery efficiency and Cu content in copper sulfide mineral samples. The experiment was conducted by varying the pH (6, 8, 10, and 12) and using different types of collectors, namely Xanthate, Potassium Amyl Xanthate (PAX), Diethyl Dithiophosphate (DTP), and a combination of PAX + DTP. Control variables included flotation time (5, 10, 15, 20, and 25 minutes), collector concentration at 50 mg/L, particle size <75 µm, and the use of Frother Methyl Isobutyl Carbinol (MIBC) at a concentration of 10 mg/L. Modifiers such as NaOH and H₂SO₄ were used to adjust the pH, while Copper Sulfate (CuSO₄) served as an activator and Sodium Metabisulfite (Na₂S₂O₅) as a depressant. The results showed that variations in pH and collector types significantly influenced recovery efficiency and Cu content in the concentrate. In general, the highest recovery efficiency was achieved at pH 10 with the combination of PAX + DTP, which resulted in a higher Cu content compared to other single collectors. This combination was able to improve recovery efficiency to over 75%, with Cu content in the concentrate reaching 28%. Therefore, the findings suggest the use of a collector combination and pH optimization as strategies to enhance the performance of copper sulfide flotation.